Autophagy is involved in assisting the replication of Bamboo mosaic virus in Nicotiana benthamiana - Huang, Ying-Ping; Huang, Ying-Wen; Hsiao, Yung-Jen; Li, Siou-Cen; Hsu, Yau-Huei; Tsai, Ching-Hsiu (Journal of experimental botany, 2019)
Autophagy plays a critical role in plants under biotic stress, including the response to pathogen infection. We investigated whether autophagy-related genes (ATGs) are involved in infection with Bamboo mosaic virus (BaMV), a single-stranded positive-sense RNA virus. Initially, we observed that BaMV infection in Nicotiana benthamiana leaves upregulated the expression of ATGs but did not trigger cell death. The induction of ATGs, which possibly triggers autophagy, increased rather than diminished BaMV accumulation in the leaves, as revealed by gene knockdown and transient expression experiments. Furthermore, the inhibitor 3-methyladenine blocked autophagosome formation and the autophagy inducer rapamycin, which negatively and positively affected BaMV accumulation, respectively. Pull-down experiments with an antibody against orange fluorescent protein (OFP)-NbATG8f, an autophagosome marker protein, showed that both plus- and minus-sense BaMV RNAs could associate with NbATG8f. Confocal microscopy revealed that ATG8f-enriched vesicles possibly derived from chloroplasts contained both the BaMV viral RNA and its replicase. Thus, BaMV infection may induce the expression of ATGs possibly via autophagy to selectively engulf a portion of viral RNA-containing chloroplast. Virus-induced vesicles enriched with ATG8f could provide an alternative site for viral RNA replication or a shelter from the host silencing mechanism.